Pengaruh Gaya Kepemimpinan terhadap Kinerja Pegawai pada Kantor Distrik Ayamaru Timur Kabupaten Maybrat - Murafer, Yance; Longkutoy, Meyta; Timisela, Yanti M. (Attractive : Innovative Education Journal, 2022)
This study attempts to analyze style leadership influence on the performance of employees at the district ayamaru east maybrat district. The method of analysis the data used was the quantitative analysis. Testing significant through (t-test), using linear regression simple and coefficients determinansi (r2). The population of the research is all employees in Office district ayamaru eastern district maybrat. sample respondents were 48. The primary data was obtained through interviews, the questionnaire and study documentation. from the results of data processing simple linear regression analysis using the SPSS for windows version 25 program, the regression equation Y = 7.814 + 0.696X, the regression coefficient value of 0.696 means that every time there is a change and an addition of one percent in the Leadership Style variable, the Employee Performance variable will increase. of 0.696, if the Leadership Style variable is zero, then Employee Performance has a value of 7.814. In the coefficient of determination test, R square is 53.46%, meaning that leadership style has an effect on employee performance by 53.46%, while the remaining 46.4% is influenced by other factors not analyzed in this study, namely work culture. The results of the t-test, where t count 7.525 > t table 1.6787, it can be said that the Leadership Style variable has a positive and significant effect on employee performance. Keywords: Leadership Style, Employee Performance, Employee Leadership Style